1991
DOI: 10.1038/clpt.1991.118
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-dose pharmacokinetics of ganglioside GM1 after intravenous and intramuscular administration to healthy volunteers

Abstract: Ganglioside GM1 multiple-dose pharmacokinetics were investigated in five healthy male volunteers. Doses of 100 mg were administered either intravenously or intramuscularly for 21 days, and the washout was followed-up for a further 21 days. The highly specific binding of the beta-subunit of cholera toxin was used to quantify ganglioside GM1 levels in plasma, urine, and feces. This dose regime increased the ganglioside GM1 steady-state plasma levels two to three orders of magnitude above the endogenous levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…2 D). Plasma GM1 has also been shown to be maintained above the endogenous GM1 level for several days after cessation of administration once steady-state levels have been achieved (Rost et al, 1991). We therefore included a 1 week washout period for the GM1 study.…”
Section: Peripheral Administration Of the A␤ Sequestering Agent Gm1 Amentioning
confidence: 99%
“…2 D). Plasma GM1 has also been shown to be maintained above the endogenous GM1 level for several days after cessation of administration once steady-state levels have been achieved (Rost et al, 1991). We therefore included a 1 week washout period for the GM1 study.…”
Section: Peripheral Administration Of the A␤ Sequestering Agent Gm1 Amentioning
confidence: 99%
“…In a pharmacokinetics study in lung cancer, the subjects in the loading dose treatment arm showed similar results as above. Plasma levels returned to basal levels within 24 h of administration and there was no evidence of accumulation ( 75 , 76 ).…”
Section: Potency and Pharmacokinetics Implicationsmentioning
confidence: 99%
“…Solid-phase synthesis is the only technique approved for the clinical production of Tα1. Tα1 is commonly provided twice a week through subcutaneous injection, with a conventional dosage range of 0.8-6.4 mg and a multi-dose range of 1.6-16 mg [26]. A pharmacokinetic study showed that after subcutaneous injection, Tα1 is well-absorbed in the body, and its peak blood drug concentration (Cmax, the highest blood drug concentration after administration) is reached at 1-2 h, with a plasma half-life (t1/2, an estimate of the time it takes for the concentration or amount in the body Furthermore, electrostatic interactions may enhance the binding of Tα1 to hyaluronic acid (HA) and interfere with the binding of HA to CD44 and the motor receptor RHAMM, inhibiting viral infection progression [24].…”
Section: The Protein Binding Properties and Biosafety Of Tα1mentioning
confidence: 99%